2012
DOI: 10.2147/jpr.s28636
|View full text |Cite
|
Sign up to set email alerts
|

Investigating patient expectations and treatment outcome in a chronic low back pain population

Abstract: ObjectiveThis study aimed to measure the outcomes that patients consider clinically meaningful across four treatment domains – (1) pain, (2) fatigue, (3) emotional distress, and (4) level of interference – and determine if patients met their own success criteria. Additionally, the role of expectations in treatment outcome was examined. This study also aimed to determine how change in levels of pain, fatigue, disability, and level of interference varied according to the type of treatment delivered to participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In a larger randomized controlled trial, prognostic variables for responders should be identified to foster the allocation of patients to treatment that is appropriate for them. Because existing treatments only have low to moderate effects (57) and fail to meet patients’ success criteria (8, 9), our results are promising because the treatment seemed to meet patients’ success criteria and clinically relevant changes were suggested for half of the treated patients. However, due to our pilot study design, results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a larger randomized controlled trial, prognostic variables for responders should be identified to foster the allocation of patients to treatment that is appropriate for them. Because existing treatments only have low to moderate effects (57) and fail to meet patients’ success criteria (8, 9), our results are promising because the treatment seemed to meet patients’ success criteria and clinically relevant changes were suggested for half of the treated patients. However, due to our pilot study design, results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 82%
“…Although there are many approaches to treating nsCBP, unfortunately, treatment in these patients has often limited success (57) and fails to meet patients’ success criteria (8, 9). This might be the case because many of nsCBP patients report high emotional distress (1013), but particularly for nsCBP patients with high degrees of emotional distress, classic pain-psychotherapeutic approaches are often insufficient (14).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three papers discussed the patients’ perceived role of the medical practitioner in the management of LBP[ 25 , 37 , 38 , 40 , 43 , 50 , 52 , 53 , 59 , 61 , 67 , 69 , 73 , 74 , 79 85 ]. A consistent theme that emerged from patients recruited from general practice [ 69 , 81 , 84 , 86 ], the community[ 43 , 60 ] and tertiary care was the need to obtain a diagnosis and a cause of the pain[ 37 , 38 , 59 , 60 , 67 , 69 , 79 , 81 , 84 ]. Other reasons for seeking medical care included a need to obtain medications for pain relief[ 50 , 51 , 61 , 80 ], to receive advice and discussion of options for LBP management[ 38 , 61 , 85 ], to receive sickness certification and legitimation of their back pain[ 25 , 51 , 52 ].…”
Section: Results Of Reviewmentioning
confidence: 99%
“…Most CLBP patients have tried several interventions to cure their pain or get more control over it 1. The search for full recovery can involve great effort; despite this effort, the majority of attempts remain unsuccessful 24. Repeated failures in controlling pain can lead to less pain tolerance, more worry, and fear or catastrophic thinking, thus opening up new areas of concern 57…”
Section: Introductionmentioning
confidence: 99%